Effect of Mouth Rinses with Fluoride and Trimetaphosphate on Enamel Erosion: An in vitro Study - Manarelli, M. M. [UNESP]; Vieira, A. E. M. [UNESP]; Matheus, A. A. [UNESP]; Sassaki, K. T. [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Karger, 2011)
The effect of mouth rinses containing fluoride (100 mu g/ml) and sodium trimetaphosphate (TMP) on enamel erosion was evaluated in vitro. Bovine enamel blocks were subjected to erosive challenges 4 times per day for 5 min, followed by treatment with placebo, 225 mu g F/ml, 100 mu g F/ml, 100 mu g F/ml and TMP (0.2, 0.4 and 0.6%) solutions (30 s) and storage in artificial saliva, over a duration of 5 days. TMP groups showed lower enamel wear than fluoride-only and placebo groups (p < 0.05). Addition of TMP at a TMP:NaF molar proportion between 1.24:1 and 3.72:1 to a solution containing 100 mu g F/ml presented a greater protective effect under erosive conditions than a solution containing 225 mu g F/ml, in the absence of TMP. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Enamel; Erosion; Fluoride; Mouth rinses; Phosphate